Outbreak of SARS-CoV-2 in a teenage discotheque in Northern Ireland—November 2021. (October 2022) - McAleavey, P.; Rainey, E.; McKaig, C.; Richardson, C.; Anderson, C.; Tilley, C.; Kmiecik, E.D.; Dallat, M.; Stevens, H.; Sheridan, P.; Bennett, D.
Abstract: Objectives: To report key findings associated with an outbreak of SARS-CoV-2 following a teenage disco in Northern Ireland. Study design: Observational case series. Methods: A case was defined as an individual who attended the event with a positive SARS-CoV-2 result between 6th and 20th November 2021. Demographic and clinical information, including symptom status, date of onset and school attended, were recorded during contact tracing. Vaccination status was derived from the COVID-19 Vaccine Management System. Forty-five samples associated with the outbreak were sequenced as part of the NI Whole Genome Sequencing (WGS) programme. Results: Only 2.4% (5/205) of cases received a COVID-19 vaccine more than 14 days before the event. 84.9% (174/205) had received no vaccine at the time of the event and 12.7% (26/205) had been vaccinated within 14 days, offering only limited disease protection. The AY4.2.2 lineage of two cases who attended the event after symptom onset was found in 69% of sequenced outbreak cases. Conclusions: This study demonstrates extensive COVID-19 transmission in largely unvaccinated teenagers in an indoor venue with limited social distancing, close social contact and mixing, limited ventilation and singing and shouting. Public Health authorities developing COVID-19 entertainment regulations should consider congregations of teenagers in these settings, especially if vaccination rates are low in this group or they are not eligible for vaccination at that time. Public communications should be developed to ensure young people with COVID-19 symptoms follow public guidance regarding self-isolation and in particular avoid indoor events with larger numbers.